Sincerity, Responsibility, and Moral Conduct: The Relevance of Ibn Taimiyah’s Ethics in Early Childhood Teaching Practice - Adillah Shinta Al Azizati; Taufikin; A’yuna Dzil Ma’unah; Vega Faisal Amri (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The ethical conduct of educators plays a foundational role in shaping student character, yet contemporary early childhood education often lacks integrative models rooted in spiritual and moral traditions. Despite the richness of Islamic pedagogical heritage, particularly the thought of Ibn Taimiyah, its practical application in modern classrooms remains underexplored. This study aims to examine how the ethical values articulated by Ibn Taimiyah are understood, enacted, and remain relevant within a contemporary early childhood educational context. Using a qualitative case study approach, the research was conducted at TK Muslimat Malihatul Hikam in Lamongan, Indonesia. Data were collected through in-depth interviews with 17 informants (one principal, eleven teachers, and five parents), direct classroom observations, and document analysis. Data were analyzed using Miles and Huberman’s interactive model. Findings indicate that teachers demonstrate a comprehensive understanding and application of core ethical principles, including sincerity, responsibility, patience, and moral conduct. These values are manifested through consistent professional discipline, spiritual routines, compassionate communication, and ethical use of technology. The ethical framework espoused by Ibn Taimiyah proved adaptable and effective in reinforcing holistic character development and promoting a spiritually infused teaching environment. This study affirms the empirical relevance of classical Islamic educational ethics in contemporary practice and highlights the potential for bridging traditional moral philosophy with current pedagogical needs in early childhood education.